Diet and lifestyle interventions in postpartum women in China: study design and rationale of a multicenter randomized controlled trial - Bao, Wei (BioMed Central, 2010)
BACKGROUND: "Doing the month", or "sitting month", is a traditional practice for postpartum women in China and other Asian countries, which includes some taboos against well-accepted healthy diet and lifestyles in general population. Previous studies have shown this practice may be associated with higher prevalence of postpartum problems. The current multicenter randomized controlled trial (RCT) aims to evaluate outcomes of diet and lifestyle interventions in Chinese postpartum women. METHODS/DESIGN: The current multicenter RCT will be conducted in three representative areas in China, Shandong province, Hubei province and Guangdong province, which locate in northern, central and southern parts of China, respectively. Women who attend routine pregnancy diagnosis in hospitals or maternal healthcare centers will be invited to take part in this study. At least 800 women who meet our eligibility criteria will be recruited and randomly assigned to the intervention group (n > = 400) and the control group (n > = 400). A three-dimension comprehensive intervention strategy, which incorporates intervention measures simultaneously to individual postpartum woman, their family members and community environment, will be utilized to maximize the effectiveness of intervention. Regular visiting and follow-up will be done in both group; nutrition and health-related measurements will be assessed both before and after the intervention. DISCUSSION: To our knowledge, this current study is the first and largest multicenter RCT which focus on the effectiveness of diet and lifestyle intervention on reducing the incidence rate of postpartum diseases and improving health status in postpartum women. We hypothesize that the intervention will reduce the incidence rates of postpartum diseases and improve nutrition and health status due to a balanced diet and reasonable lifestyle in comparison with the control condition. If so, the results of our study will provide especially important evidence for changes in both the concept and action of traditional postpartum practice in China. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT01039051.